The Qur'ān and Hadīth as the Mediator of Fanaticism of Exclusive Islam and Inclusive Islam Factions - mahmudi, Kholis ali; Zahra, Bahezta Lama'a (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
This study examines the function of the Quran and Hadith as a solution to overcome the fanaticism of exclusive Islam and inclusive Islam using a literary-based qualitative approach. The results of this study state that, peace is a behavior that reflects the values of mutual love, compassion, belonging between parties without denying one of the parties due to its limitations. Islam as a religion that loves peace has several ways to create this situation with the sources of the Quran and Hadīth, such as examples of tolerance, freedom, upholding justice and prohibiting forms of injustice practices. If all of these elements are of concern so that they can be applied in the order of people's lives, of course, the conclusions of the birth of harmony between people for the achievement of world peace.